Solution of Linear Fractional Programming Problem by Fourier-Motzkin Elimination Technique - Pawan Kishore Tak, Gyan Shekhar, Sanjay Jain, Adarsh Mangal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research paper, Fourier-Motzkin elimination technique is suggested to solve LFPP, which is based upon the concept of bounds. The proposed approach is computationally more efficient and easy to understand as compared to the traditional simplex method. An illustration has been given at the end.